Sembe' Traditional Medicine Practice Lombok Community in The Perspective of Socio-Culture and Islamic Aqidah - Wafik Aziza; Suhada Suhada; Sukarta Sukarta (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This research examines the practice of Sembe traditional medicine in Lombok society in the context of socio-cultural and Islamic aqidah. The issue raised is the community's perception of the harmony of Sembe practice with Islamic teachings and its impact on health and social cohesiveness. The purpose of this study is to analyse the interaction between cultural values and religious principles in Sembe practice. The method used was a descriptive qualitative approach through in-depth interviews and participatory observation in several villages in West Lombok. The results showed that the practice of Sembe is still believed and accepted by the community, despite criticism from some religious leaders who consider some aspects of it deviating from Islamic teachings. The conclusion of this study emphasises the importance of harmonising cultural practices with religious values to create a more inclusive understanding in society.key four words or phrases. The keywords are written in Indonesian in alphabetical ordern